A Descent into the Nuage: The Maelstrom of Transposon Control - O’Donnell, Kathryn A. (2008)
In this issue of Developmental Cell, Soper and colleagues (2008) report that the mammalian MAELSTROM (MAEL) protein is critical for transposon silencing in the male germ line. Loss of MAEL is associated with meiotic failure and DNA damage, suggesting that efficient transposable element restraining mechanisms must be in place for the preservation of germ line integrity.